2012
DOI: 10.1055/s-0032-1304544
|View full text |Cite
|
Sign up to set email alerts
|

High Mortality in Late Octogenarians Undergoing Isolated Aortic Valve Replacement for Aortic Valve Stenosis: EuroSCORE Underestimates Mortality in this Cohort

Abstract: Mortality after AVR in the late octogenarians was very high, and was underestimated by EuroSCORE in this patients group. In late octogenarians, catheter-based aortic valve implantation despite relative low EuroSCORE level could be considered as a reasonable alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Gender does not have a significant impact and at 5 years mortality is not significantly different between males and females, although higher in (8.0% vs. 5.9%, p = 0.332) [11,21]. The lack of differences in early death odds of postoperative hospital death that emerges from our study is in agreement with what was found by Abel and colleagues in octogenarians [8] and by Kurlansky et al [1], on the contrary, contrasts with that found by Kamiya et all [10]. It is difficult to explain why an initial greater survival of the under 85s and therefore less risk then loses significance.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Gender does not have a significant impact and at 5 years mortality is not significantly different between males and females, although higher in (8.0% vs. 5.9%, p = 0.332) [11,21]. The lack of differences in early death odds of postoperative hospital death that emerges from our study is in agreement with what was found by Abel and colleagues in octogenarians [8] and by Kurlansky et al [1], on the contrary, contrasts with that found by Kamiya et all [10]. It is difficult to explain why an initial greater survival of the under 85s and therefore less risk then loses significance.…”
Section: Discussionsupporting
confidence: 87%
“…Likewise with regard to pre-operative cardiogenic shock, it is understandable how the presence of severe cardiac pump impairment -and pre-and post-operative, requiring pharmacological support and with IABP, can influence the outcome and the intrinsic mortality related to cardiogenic shock itself, as well as worsening of chronic renal insufficiency or the onset of acute new renal failure. On the other hand, the literature confirms that in the over 85 yrs there is a persistence/appearance of a severely reduced left ventricular function (OR 8.0, 95% CI 1.2-53.5, p = 0.032) [10].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast, data from a German study showed that mortality after isolated AVR in late octogenarians was underestimated by the EuroSCORE [17]. A similar underestimation of risk may occur with renal transplant patients.…”
Section: Discussionmentioning
confidence: 88%